2005
DOI: 10.1097/00000542-200511000-00008
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Driving Performance of Ambulatory Surgical Patients after General Anesthesia?

Abstract: Patients showed lower alertness levels and impaired driving skills preoperatively and 2 h postoperatively. Based on driving simulation performance and subjective assessments, patients are safe to drive 24 h after general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…In a prospective study of 20 patients undergoing knee arthroscopy under GA, patients demonstrated lower alertness levels and impaired driving skills preoperatively and two hours postoperatively. 120 These parameters returned to normal within 24 hr, providing objective evidence that it is reasonable for patients to resume driving 24 hr after surgery. One reservation with interpreting studies addressing post-operative cognitive dysfunction is that most studies do not address the component of cognitive function most likely being altered by sedative or general anesthetic drugs.…”
Section: Driving Issuesmentioning
confidence: 78%
“…In a prospective study of 20 patients undergoing knee arthroscopy under GA, patients demonstrated lower alertness levels and impaired driving skills preoperatively and two hours postoperatively. 120 These parameters returned to normal within 24 hr, providing objective evidence that it is reasonable for patients to resume driving 24 hr after surgery. One reservation with interpreting studies addressing post-operative cognitive dysfunction is that most studies do not address the component of cognitive function most likely being altered by sedative or general anesthetic drugs.…”
Section: Driving Issuesmentioning
confidence: 78%
“…The participants recovered their performance in the Number Connecting Test and driving simulator two hours after the procedure. Chung et al [26] demonstrated that the recovery assessed with a driving simulator, polysomnography, and subjective scales allowed safe driving only after at least 24 hours following anaesthesia with fentanyl, midazolam, and propofol. The choice of a drug used during anaesthesia is crucial to fast recovery afterwards, and this means that there is a need for further studies comparing the effectiveness of cognitive recovery after the administration of different anaesthetic schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al 21 compared the driving performance (in a simulator) in patients who had their surgery performed under general anesthesia with healthy, nonanesthetized controls. Under these more realistic circumstances, simulated driving in patients was impaired both pre-and postoperatively.…”
Section: Driving After Ambulatory Surgerymentioning
confidence: 99%